1986
DOI: 10.1159/000167329
|View full text |Cite
|
Sign up to set email alerts
|

Role of Baroreflex Activation in the Regional Hemodynamic Effects of the Beta-Blockers Tertatolol and Propranolol in Conscious Spontaneously Hypertensive Rats

Abstract: The effects of the β-adrenoceptor-blocking drugs tertatolol and propranolol on regional hemodynamics were compared in intact and sinoaortic denervated (SAD) conscious spontaneously hypertensive rats (SHR). Miniaturized Doppler flow probes were used for the continuous determination of changes in flows and resistances in the renal, mesenteric, and hindquarter vascular beds. In intact animals 5 mg/kg propranolol i.v. caused an initial increase and a later gradual fall in mean arterial blood pressure (MAP) and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
3
5
0
Order By: Relevance
“…These results are in agreement with those obtained in pharmacological trials both in intact hypertensive ani mals [14] and in isolated perfused kidney [19]. The mechanisms by which tertatolol can exert this antivasoconstrictive effect at the level of renal circulation remain to be clarified.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in agreement with those obtained in pharmacological trials both in intact hypertensive ani mals [14] and in isolated perfused kidney [19]. The mechanisms by which tertatolol can exert this antivasoconstrictive effect at the level of renal circulation remain to be clarified.…”
Section: Discussionsupporting
confidence: 89%
“…An immediate reduction in heart rate and cardiac index was observed but systemic pressure was not modified. This stability of blood pres sure following a single dose of (5-blocker is due to reflex stimulation of the baroreceptors secondary to reduced cardiac output, which leads to an increase in vascular systemic resistance [14], Despite these modifications of systemic hemodynam ics with the two drugs, renal blood flow was not affected after tertatolol, whereas it significantly decreased after propranolol.…”
Section: Discussionmentioning
confidence: 98%
“…This discrepancy was also shown by Struyker-Boudier et al [19] who reported a preservation of renal blood flow with a decrease in renal vascular resistance after tertatolol injection in spontaneously hy pertensive rats, whereas propranolol produced renal va soconstriction with a decrease in renal blood flow.…”
Section: Discussionsupporting
confidence: 60%
“…a redistribution towards the hepatosplanchnic circulation has also been shown [19], Finally, the best example is given by the (3-blocking drug tertatolol: while cardiac output is reduced and total peripheral resistance elevated, a striking vasodilation in the kidney is ob served at the same time. Following acute administration, the preserved renal plasma flow observed with tertatolol appears to be the consequence of a lack of vasoconstric tion within the kidney; this takes place in the context of a systemic vasoconstriction [20][21][22]. Following chronic administration, the preserved or increased renal plasma flow appears to be the consequence of renal vasodilation, this takes place in the context of the long-term adapta tion of vascular resistance [20][21][22][23].…”
Section: Redistribution O F Vascular Resistancementioning
confidence: 99%
“…Following acute administration, the preserved renal plasma flow observed with tertatolol appears to be the consequence of a lack of vasoconstric tion within the kidney; this takes place in the context of a systemic vasoconstriction [20][21][22]. Following chronic administration, the preserved or increased renal plasma flow appears to be the consequence of renal vasodilation, this takes place in the context of the long-term adapta tion of vascular resistance [20][21][22][23]. Furthermore, the vasodilation is more effective in the presence of an ini tial background of renal vasoconstriction, as can be observed in sustained essential hypertension, thus result ing in an absolute increase in renal plasma flow.…”
Section: Redistribution O F Vascular Resistancementioning
confidence: 99%